Executive functions in students with dyslexia. Educational implications - Piedra-Martínez, Elisa; Soriano-Ferrer, Manuel (Pulso. Revista de educación, 2019)
Behavioral ratings of executive functions (EFs) in children, adolescents, and adults with dyslexia are scarce and limited. Therefore, this study tries to analyze transversally clinically significant deficiencies in EFs in three groups of people with dyslexia (children, n = 37; adolescents, n = 19; and adults, n = 39), using a rating scale designed to measure executive behaviors in everyday activities. The results showed that the different informants employed (parents, teachers, selfreporters and observers) reported between 10% and 80% of children, adolescents and adults clinically impaired in tasks related to cognitive regulation (e.g., initiative, working memory, plan-organize, organization of materials and task monitor). Along the same lines, between 5% and 10% were also identified with deficiencies related to the regulation of behavior and emotions. In addition, teachers as well as adolescents and adults themselves identify more subjects with clinically significant deficiencies through self-reports. Results are discussed in relation to the educational assessment and intervention in the EFs.